SCIENTIFIC-THEORETICAL FOUNDATIONS OF CIVIL PROCESS STAGES - Davlatjon Khabibullaev (European Science Publishing, 2024)
This article presents the concept of stages of civil proceedings and the opinion that the execution of judicial acts is the last stage, as well as relevant scientific and theoretical recommendations.
Keywords: civil process, court, stage, judge, judicial act, car.